Systematic Quality Management in Vocational Educational Institutes: Role of Teachers in Development of Organizational Quality - Gisela Wiesner; Nurhening Yuniarti (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
A quality management system for vocational educational institutes is a system aimed at ensuring the quality goals of vocational education are achieved to meet the quality standards and develop the quality work. In practice, teachers play a vital role because the key elements in a quality assurance system are strongly related to teachers especially the learning process as the spearhead of the success of vocational education. In addition, most activities undertaken in vocational education involve teacher participation. Therefore, teachers hold a great responsibility in the successful implementation of the educational quality management system. The main point to be emphasized is how a teacher has a suitable common understanding of quality. Understanding the quality drives all activities undertaken by teachers to be quality improvement oriented.